ANALISIS PERMINTAAN BUAH PISANG OLEH PEDAGANG GORENGAN DI KOTA DENPASAR, BALI - Suparyana, Pande Komang (Agrimeta: Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2017)
The aims of this study are finding out factors influencing demand, price,and cross elasticies of demand for bananas by fried merchant in Denpasar. The study focuses on fried merchant in Denpasar City including 70 respondents. Data were analyzed using multiple linear regression considering economic, econometrics and statistics criteria.Based on the linear regression analysis, the demand model for bananas by fried merchant in Denpasar is lnY = -20,832 + 0,073 lnX1 ? 0,076 lnX2 ? 0,044 lnX3 + 0,49 lnX4 +1,025 lnX5 + 0,955 lnX6 ? 0,025 lnX7 +µi.All independent variables are simultaneously significant affecting demand for bananas by fried merchant in Denpasar. Partially, prices of frying oils and income significantly affecting demand for bananas by fried merchant. Meanwhile, price of bananas, price of tofu, price of tempeh, price of flour, and cost of rent the place do not have significant effect on demand for bananas. Price elasticity of demand for bananas shows an inelastic figure (e<1), implying that demand for bananas is not responsive to the price changes. A positive sign in the value of the income elasticity indicates that banana is a normal good. Sign of the cross-price elasticity of tofu and tempeh prices was negative, referring that these goods are complementary to bananas.